Panitumumab‐based maintenance after oxaliplatin discontinuation in metastatic colorectal cancer: A retrospective analysis of two randomised trials. Issue 2 (24th January 2019) - Modest, Dominik Paul; Rivera, Fernando; Bachet, Jean‐Baptiste; de Braud, Filippo; Pietrantonio, Filippo; Koukakis, Reija; Demonty, Gaston; Douillard, Jean‐Yves
Abstract : Panitumumab is approved for RAS wild‐type metastatic colorectal cancer and was evaluated in Phase III (PRIME, NCT00364013) and Phase II (PEAK, NCT00819780) first‐line randomised studies. This retrospective analysis of these trials investigated efficacy and toxicity of panitumumab‐based maintenance after oxaliplatin discontinuation in RAS wild‐type patients. First‐line regimens were FOLFOX4 ± panitumumab in PRIME and mFOLFOX6 plus panitumumab or mFOLFOX6 plus bevacizumab in PEAK. Outcomes included median progression‐free survival (PFS) and overall survival (OS), from randomisation and oxaliplatin discontinuation, and toxicity. Overall, median duration of panitumumab plus 5‐fluorouracil/leucovorin (5‐FU/LV) maintenance was 21 (interquartile range: 11–41) weeks; that of 5‐FU/LV ± bevacizumab maintenance was 16 (6–31) weeks. Median OS from randomisation was 40.2 (95% confidence interval: 30.3–50.4) and 39.1 (34.2–63.0) months for panitumumab plus 5‐FU/LV maintenance and 24.1 (17.7–33.0) and 28.9 (21.0–32.0) months for 5‐FU/LV ± bevacizumab maintenance in PRIME and PEAK, respectively. Median PFS from randomisation was 16.6 (11.3–23.6) and 15.4 (11.6–18.4) months for panitumumab plus 5‐FU/LV maintenance and 12.6 (9.4–16.2) and 13.1 (9.5–16.6) months for 5‐FU/LV ± bevacizumab maintenance in PRIME and PEAK, respectively. From oxaliplatin discontinuation, median OS was 33.9 (24.7–42.8) and 33.5 (24.5–54.9) months for panitumumab plus 5‐FU/LV maintenance and 16.4 (12.4–24.1) and 23.3 (15.7–26.3) months for 5‐FU/LV ± bevacizumab maintenance in PRIME and PEAK, respectively; PFS was 11.7 (7.8–19.2) and 9.7 (5.8–14.8) months and 7.1 (5.6–10.2) and 7.0 (3.9–10.6) months, respectively. The most frequently reported adverse events were rash, fatigue and diarrhoea. Maintenance of panitumumab plus 5‐FU/LV after oxaliplatin discontinuation was well tolerated and may be an acceptable treatment paradigm for patients demonstrating a good response to first‐line treatment. Prospective studies are warranted. Abstract : What's new? Panitumumab is an anti‐EGFR antibody used in the treatment of RAS wild‐type metastatic colorectal cancer. But is it useful for long‐term therapy in these patients, especially after more toxic therapies like oxaliplatin are discontinued? In this retrospective analysis, the authors found that a maintenance regimen including panitumumab was well tolerated and may be associated with better outcomes than non‐panitumumab strategies. Patients who received panitumumab‐based maintenance therapy were also more likely to have had a good response to first‐line treatment. The results from this study indicate that further, prospective studies are warranted.